r=-6
2007-01-21 07:53:05
·
answer #1
·
answered by nexusdhr84 2
·
0⤊
0⤋
2r+6=r
subtract r from both sides
r+6=0
subtract 6 from both sides
r=-6
2007-01-21 15:55:01
·
answer #2
·
answered by Ben B 4
·
0⤊
0⤋
you want to set the equation to 0 so 2r-r+6=0. Then by simplfying you get r+6=0 and trying to isolate r you get r= -6
2007-01-21 15:56:12
·
answer #3
·
answered by taramarie 2
·
0⤊
0⤋
First: subtract "2r" from both sides....
2r - 2r + 6 = r - 2r
6 = - r
-r = 6
Sec: the coefficient/variable "r" can't be negative - change every sign in the equation...
r = - 6
2007-01-21 16:02:04
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2r+6=r
2r=r-6
-r = -r
r=-6
2007-01-21 15:54:37
·
answer #5
·
answered by italianwiseass13 2
·
0⤊
0⤋
2r+6=r
-r -r
r+6=0
-r
6=-r
*.1 *-1
-6=r
2007-01-21 15:56:23
·
answer #6
·
answered by cltcprd33 2
·
0⤊
0⤋
2r-r+6=r-r
r+6=0
r+6-6=0-6
r=-6
2007-01-21 16:12:04
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
r = -6
2(-6) +6 = -6
-12 + 6 = -6
-6 = -6
0 = 0
2007-01-21 15:58:24
·
answer #8
·
answered by diogenese19348 6
·
0⤊
1⤋
r = -6
2r+6=r
You want to get r by itself.
Subtract 2r from both sides
6=-r
We need a positive r, so divide both sides by -1.
-6=r
or
r=-6
2007-01-21 15:54:12
·
answer #9
·
answered by dramaman22 3
·
0⤊
1⤋
2r + 6 = r......Subtract r from each side
r + 6 = 0........subtract 6 from each side
r = -6
2007-01-21 15:53:57
·
answer #10
·
answered by rosie recipe 7
·
0⤊
0⤋